Analysis of Light Pollution in Ticino region during the period 2011-2016. (December 2020) - Cereghetti, N.; Strepparava, D.; Bettini, A.; Ferrari, S.
Highlights: A study on the nighttime skyglow data collected in a Swiss region is presented. The approach adopted for the time-series analysis data has been described. The pollution level in representative areas of Ticino region has been assessed. The evolution trend of light pollution in Ticino region has been evaluated. Abstract: Since 2002, the Environmental Observatory of Southern Switzerland (OASI) has monitored a remarkable set of environmental parameters with the purpose of performing an enhanced observation of the regional environmental conditions. Since 2011, a campaign for the supervision of the artificial nighttime skyglow has been included in the OASI monitoring system exploiting the collaboration with DarkSky association. This network monitors the light pollution in several areas of Ticino, the southernmost Swiss Canton bordering Italy. It consists of multiple stations, which continuously measure the sky brightness. The University of Applied Sciences and Arts of Southern Switzerland, in collaboration with Politecnico di Milano, introduces the results of a study regarding the skyglow evolution during the period 2011-2016. The time-series of the OASI network were pre-processed to detect and discard data affected by natural perturbing events, such as moon and clouds presence and sun effect during twilights. In a second time, a distribution analysis of the data and an evaluation of the brightness trend during the considered period were performed. The results show that light pollution in Ticino is strictly influenced by the northern area of the nearby Italian Lombardy region and that during the surveyed years a decreasing of the pollution occurred.